Tiktok Analysis Sense Of Humor Bintang Emon To Government Criticism - Elyondi, Brata Ogin; Meidi Budi Utomo, Djarot (Indonesian Journal of Public Policy Review, 2022)
Tiktok social media can be used as a medium where people can express themselves. This activity of expressing can include the outpouring of his heart and personal experiences that are told through videos, music and some symbols in the tiktok media. One of the famous content creators on social media tiktok is Bintang Emon. Bintang Emon criticizes the government through a tiktok video. This research method uses a qualitative research type. Primary data sources are taken from Bintang Emon's tiktok content and secondary data sources are obtained from journals and previous research. The data analysis technique of this research is data reduction, data presentation and conclusion drawing. The results of this study state that the content of government criticism carried out by Bintang Emon is starting from criticism of the legal system in Indonesia which is blunt up and sharp down so that people with lower economies will get cruel punishments compared to acts of corruption committed by upper class people. . Furthermore, the content of Bintang Emon's criticism includes the ratification of the Omnibus Law which of course also harms the lower economic community. Then, the contents of the next criticism are related to the motto of Puan Maharani who considers Indonesia to have good cooperation but in fact the condition of Indonesia is still a lot of conflicts.